Transport and Surface Properties of Molten Cd-Zn Alloys - Koirala, I; Singh, B.P.; Jha, I.S. (Journal of Institute of Science and Technology, 2015)
Simple statistical theory has been used to report the thermo-physical properties of mixing in liquid Cd-Zn alloys. The energetic of mixing in liquid alloys has been analyzed through the study of surface properties (surface tension, surface concentration) and transport properties (diffusivity, viscosity). Negative deviation from Raoultian behaviour has been observed in the computed mixing parameters (viscosity, surface tension) of the alloys. The computed results support a weak phase-separation tendency in molten Cd-Zn system. Journal of Institute of Science and Technology, 2014, 19(1): 14-18